Tinjauan Singkat Sistem PLTP Siklus Gabungan Sarulla Menggunakan Ormat Energy Converter - Harefa, Jonius Christian; Sinaga, Nazaruddin (TEKNIKA, 2021)
Geothermal energy is not fully utilized in Indonesia. Until 2020, the realization of geothermal development into electricity is 2,130.7 MW. One of the geothermal power plants (PLTP) in Indonesia that has been operating is the Sarulla Geothermal Power Plant. The total capacity produced by Sarulla is 330 MW. Sarulla is a Geothermal Combined Cycle that uses a binary power plant to maximize existing geothermal energy. The output of Steam Turbine Generator (STG) is utilized through the OEC Bottoming to produce 7 MW of electricity while Hot Water (Brine) is utilized through the OEC Brine to generate 15 MW of electricity. The residual steam and brine output which are generally injected directly into the injection well, with the binary technology from Ormat Energy Converter (OEC) are then utilized to maximize geothermal energy by generating electricity with a smaller capacity.